2011
DOI: 10.1073/pnas.1019079108
|View full text |Cite
|
Sign up to set email alerts
|

Fluid dynamics and noise in bacterial cell–cell and cell–surface scattering

Abstract: Bacterial processes ranging from gene expression to motility and biofilm formation are constantly challenged by internal and external noise. While the importance of stochastic fluctuations has been appreciated for chemotaxis, it is currently believed that deterministic long-range fluid dynamical effects govern cell-cell and cellsurface scattering-the elementary events that lead to swarming and collective swimming in active suspensions and to the formation of biofilms. Here, we report direct measurements of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
721
6
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 678 publications
(787 citation statements)
references
References 59 publications
(92 reference statements)
56
721
6
4
Order By: Relevance
“…Estimates suggest this requires volume fractions in the range of a few per cent, and indeed this is roughly the point at which collective behaviour begins to be seen, as discussed in § 5. The problem of cell-surface interactions with competing hydrodynamic effects and rotational Brownian motion leads to a non-trivial Kramers-like problem for escape from the surface that has only begun to be explored (Drescher et al 2011). It has been known for many years that swimming cells accumulate near surfaces.…”
Section: Surface Interactions Of Microswimmersmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates suggest this requires volume fractions in the range of a few per cent, and indeed this is roughly the point at which collective behaviour begins to be seen, as discussed in § 5. The problem of cell-surface interactions with competing hydrodynamic effects and rotational Brownian motion leads to a non-trivial Kramers-like problem for escape from the surface that has only begun to be explored (Drescher et al 2011). It has been known for many years that swimming cells accumulate near surfaces.…”
Section: Surface Interactions Of Microswimmersmentioning
confidence: 99%
“…This provides ex post facto justification for the use of Squires' result for the lateral advection of Stokeslets in explaining the infalling trajectories of colonies forming a hydrodynamic bound state. Measurements of the flow fields around individual freely swimming cells were then extended to the case of bacteria using a different method (Drescher et al 2010b(Drescher et al , 2011. Here, rather than using a tracking microscope, we adopted a fixed (horizontal) field of view on an inverted microscope, with a typically narrow focal plane width, and monitored swimming cells and advected tracer particles.…”
Section: Surface Interactions Of Microswimmersmentioning
confidence: 99%
“…These flows can be compared with flow fields from numerical computations (O'Malley & Bees, 2012). Drescher et al (2010a) measured the flow around freely-swimming bacteria. These studies again revealed stresslet behaviour in the far-field (decaying approximately as the reciprocal of the radius squared) although they reported the overwhelming importance of stochastic effects in cell-cell and cell-boundary interactions over larger distances.…”
Section: Measuring the Flowfieldmentioning
confidence: 99%
“…To calculate the enhancement ratio, we use the following parameters of the puller model (figure 2 [1,3]. Finally, the Stokes drag law holds: f p ¼ 6pbh 0 vN, where an expression for N can be found in [4].…”
Section: Comparison With Experimentsmentioning
confidence: 99%
“…Pullers typically propel themselves by executing a breaststroke-like motion with a pair of flagella attached at the front of the body (e.g. [3]). This should be compared to the propulsion of pushers such as Escherichia coli, which use a rotating flagellar bundle pushing the fluid behind the bacterial body (e.g.…”
Section: Introductionmentioning
confidence: 99%